DESKRIPSI KESULITAN GURU DALAM PEMBELAJARAN IPS PADA SMP NEGERI - Sri Fitriani; Yarmaidi Yarmaidi; Irma Lusi Nugraheni (JPG (Jurnal Penelitian Geografi), 2014)
The purpose of this study was to determine the difficulty in learning social studies in junior high school education. The method used is descriptive method. Data analysis using descriptive analysis. The results showed that: (1) most of the social studies teachers in District Martapura have difficulty in mastering the material incorporated in the IPS, the difficulty in mastering the concept of integrated learning and development learning (2) most of the difficulties in using a social studies teacher and selecting media and learning resources matching, (3) most of the social studies teachers are still difficulties in using varied teaching methods, as well as the difficulty of choosing the appropriate method to the material (4) most of the social studies teachers in District Martapura no difficulty in making lesson plans. (5) most of the social studies teachers in the district Martapura learning difficulties in making thematic mapping.Tujuan penelitian ini adalah untuk mengetahui kesulitan dalam pembelajaran IPS pada jenjang pendidikan SMP. Metode yang digunakan adalah metode deskriptif. Analisis data menggunakan analisis deskriptif. Hasil penelitian menunjukkan bahwa: (1) sebagian besar guru IPS di Kecamatan Martapura mengalami kesulitan dalam penguasaan materi yang tergabung dalam IPS, kesulitan dalam penguasaan konsep pembelajaran terpadu dan pengembangan pembelajaran (2) sebagian besar guru IPS  kesulitan dalam menggunakan dan memilih media dan sumber belajar yang cocok, (3) sebagian besar guru IPS  masih kesulitan dalam menggunakan metode pembelajaran bervariasi, serta kesulitan memilih metode yang sesuai dengan materi (4) sebagian besar guru IPS di Kecamatan Martapura tidak kesulitan dalam  membuat RPP. (5) sebagian besar guru IPS di Kecamatan Martapura kesulitan dalam membuat pemetaan pembelajaran tematik.Kata kunci : kesulitan guru, pembelajaran ips